Impact of COVID-19 Pandemic on Patients with Atopic Dermatitis - M.R. Pourani; R. Ganji; T. Dashti; S. Dadkhahfar; M. Gheisari; F. Abdollahimajd; M. Shahidi Dadras (Elsevier, 2022)
Atopic dermatitis (AD) is a chronic skin disease that may be triggered by psychological conditions and several allergens. Patients with AD may be experienced disease exacerbation due to the COVID-19 pandemic lifestyle including home-quarantine and increased stress. We obtained the electronic data of 100 AD patients admitted to our hospital from 2016 to 2019 and called them with specific phone line.Out of 100 patients, 43 were male, and 57 were female (mean age ± SD: 45.85 ± 16.90). Sixty patients (37 females and 23males; mean age: 42.22 ± 14.71) confronted disease flare-up during the COVID-19 era. Exacerbation of AD was correlated with treatment dose alteration, a lengthy history of atopic dermatitis, eczema duration, self-isolation, frequent handwashing, hand disinfection, and POEM scoring (P < 0.05). Regarding the POEM scoring, 61 patients with moderate to severe AD experienced higher anxiety than 39 patients with silent to mild AD (P = 0.013).In this study, most patients experienced disease exacerbation and perceived mild anxiety in this pandemic. Resumen: La dermatitis atópica (DA) es una enfermedad cutánea crónica que puede desencadenarse debido a situaciones psicológicas y ciertos alérgenos. Los pacientes con DA pueden haber experimentado una exacerbación de la enfermedad debido al estilo de vida durante la pandemia de la COVID-19, incluyendo el confinamiento domiciliario y el incremento del estrés. Obtuvimos los datos electrónicos de 100 pacientes con DA ingresados en nuestro hospital de 2016 a 2019, y les llamamos con una línea telefónica específica.De los 100 pacientes, 43 eran varones y 57 mujeres (edad media ± DE: 45,85 ± 16,90), de los cuales 60 (37 mujeres y 23 varones, con edad media de 42,22 ± 14,71) experimentaron el brote de la enfermedad durante la etapa de la COVID-19. La exacerbación de la DA guardó relación con la alteración de la dosis de tratamiento, un largo historial de dermatitis atópica, la duración del eccema, el autoaislamiento, la frecuencia del lavado de manos, la desinfección de las manos, y la puntuación POEM (p < 0,05). En lo referente a dicha puntuación, los 61 pacientes con DA de moderada a grave experimentaron mayor ansiedad que los 39 pacientes con DA de silente a leve (p = 0,013).En este estudio muchos pacientes experimentaron exacerbación de la enfermedad y percibieron ansiedad leve durante la pandemia.